1980-ЖЫЛЛАРДАҒЫ ҚАРАҚАЛПАҚ ПОЭМАСЫНДА ҚАҲАРМАН ОБРАЗЫНЫҢ ЖАСАЛЫЎ ӨЗГЕШЕЛИГИ (К.Каримов дөретиўшилиги мысалында) - Нуржанов, М. (FAN va JAMIYAT, 2017)
The article is devoted to the study of issues of the literary hero in the works of the famous Karakalpak poet K.Karimov. The author analyzed the poet’s skill in the description of characters.